Use of the Alcohol Use Disorders Identification Test (AUDIT) to determine the prevalence of alcohol misuse among HIV-infected individuals. (July 2013) - Surah, S; Kieran, J; O'Dea, S; Shiel, C; Raffee, S; Mulcahy, F; Keenan, E; Lyons, F
Summary: The aim of the paper is to evaluate alcohol misuse among an inner city adult HIV clinic population with AUDIT (Alcohol Use Disorders Identification Test). A cross-sectional HIV outpatient clinic analysis between 28 February 2011 and 11 March 2011 was carried out. AUDIT, demographic and clinical data were collected. Univariate analysis was performed to look for the associations between variables. Backward stepwise multivariate analyses were performed on significant variables from the univariate analysis to assess for predictors of alcohol dependence. In total, 111 patients were included (60% uptake of clinic attendees); 66% were men and 26% were hepatitis C virus (HCV) co-infected. The median AUDIT score was 5 (within normal range). Thirty-four 'AUDIT positive' cases were identified: five (4.5%) indicated consumption of hazardous levels of alcohol; 21 (19%) indicated harmful levels of alcohol; and eight (7%) were likely alcohol dependent. Younger age (<40 years old) was significantly associated with AUDIT positivity ( P = 0.006). On multivariate analysis younger age ( P = 0.045, odds ratio 13.8) and lower level of education ( P = 0.006, odds ratio 6.7) were predictive of scores indicative of alcohol dependence (AUDIT ≥20). In conclusion, younger age and lower educational levels were associated with scores consistent with alcohol dependence. AUDIT was well tolerated and easy to administer in this outpatient HIV clinic population.